FUNGSI TARI SILAT PAYUNG PADA PESTA PERKAWINAN DI DESA LUBUK AMBACANG KECAMATAN HULU KUANTAN KABUPATEN KUANTAN SINGINGI - Rama Dona E; Afifah Asriati; Indrayuda Indrayuda (SENDRATASIK UNP, 2014)
Abstract This article aimed at describing the function of “Silat Payung” dance in wedding party found in Lubuk Ambacang which still exists and develops in Lubuk Ambacang, Hulu Kuantan, Kuantan Singingi. The data of this research was descriptive quqlitative. The technique of data done through literature study, observation, interview, and documentation. The findings indicated that “Silat Payung” dance is a traditional custum yhe function of this dance are either to be performed in ritual events or as entertainment. Kata kunci : Fungsi, Pesta, Perkawinan, Tari, Silat